Social and natural contexts of the Traditions Peruvian - Huertas V., Lorenzo (2019)
This article emphasizes the proper and fair relation between some Traditions and the so-called critical span or periods of natural generic alteration. Besides, it highlights the spaces and periods of Traditions based on facts or real events without altering the historical context, but rather enriching it. In this case, Traditions become a very special historical source because they display a finesse difficult to achieve in other historical testimonies. The chronological ordering of catastrophic natural events recorded in the traditions enhance the overall picture of Peruvian disasters, from when the Inca Pachacutec ruled to the times of Palma. Thanks to the Traditions, the historians can deal with both the facts, events and structures and withtheir rumours, colours, joys, tears and losses.